P.F. Suhm som dansk Ossian-pioner i 1771 - Lundgreen-Nielsen, Flemming (Danske Studier, 2024)
P.F. Suhm (1728-98), in his life-time a celebrated Danish national historian, was a pioneer in translating selected sections from the Ossian poems dealing with the Scottish belief in the ghosts of deceased forefathers. They were included in his Danish language monograph On Odin and Heathen Mythology and Cult of Scandinavia from 1771, his source being The Works of Ossian, vols 1-2, 1765. Suhm was one of the few Danish academics at the time who read English, and his comprehensive footnotes facilitate the checking of his renditions. Also his preparatory reading of major English language works about British and North European paganism before the appearance of the Ossian texts are tracked by means of printed reference lists in his numerous earlier historical volumes. Suhm’s reliance on retelling or at least listing all possible historical sources combined with a lack of source criticism was rejected after his demise, so later scholarly evaluations of his achievements as a historian are scarce. Although Suhm thus soon was overshadowed by new theories and practical methods, his volume on Odin from Norse mythology was studied by poets even two or three decades into Danish literary romanticism of the 19th century.